The Teaching/Research Nexus And Internationalisation: An Action Research Project In Radiation Physics - Guatelli, Susanna; Layton, Catherine; Cutajar, Dean; Rosenfeld, Anatoly (Journal of University Teaching and Learning Practice, 2010)
This paper attempts to unpack the teaching and learning experiences of academics and students when a new way of teaching radiation physics was introduced. In an attempt to articulate the University of Wollongong’s commitment to the enhancement of the teaching/research nexus and to the development of learning communities, staff of the School of Physics in the Faculty of Engineering at University of Wollongong (UOW) implemented an action research project teaching scientific computing methodologies used in radiation physics to a combined laboratory class of postgraduates and undergraduates. The design of the practical laboratory classes took account of the expected heterogeneous computing skills and different knowledge of radiation physics of undergraduate and postgraduate students. Based on an earlier study, it was presumed that postgraduate students would be in a good position to support undergraduates. We illustrate how broad-based conceptions of the value of learning communities and their role in fostering the teaching/research nexus may be challenged by an internationalised student body. In this case, the previous patterns of undergraduate and postgraduate enrolments, which the pilot study had canvassed, did not hold true; almost all of the postgraduate students were international students, only recently arrived in Australia. This, along with other factors, meant that learning outcomes and students’ responses to the innovation were not what were expected. We suggest a path forward, both for the specific subject in which the innovation occurred, and for other similar attempts to bring together academics, postgraduate and undergraduate students in a nascent learning community, in the light of ongoing trends towards internationalisation.